2009
DOI: 10.1080/15476910903241704
|View full text |Cite
|
Sign up to set email alerts
|

Kupffer cell activation by ambient air particulate matter exposure may exacerbate non-alcoholic fatty liver disease

Abstract: Due to increased obesity, non-alcoholic fatty liver disease (NAFLD) is now the most prevalent liver disease in the United States. NAFLD is considered a component of metabolic syndrome, a cluster of disorders that also includes diabetes mellitus, dyslipidemia, arteriosclerosis, and hypertension. Exposure to ambient air particulate matter with aerodynamic diameters < 2.5 µm (PM 2.5 ) is a risk factor for arteriosclerosis as well as lung disease, but its effect on NAFLD is unknown. PM 2.5 induces pulmonary dysfun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 49 publications
1
55
0
1
Order By: Relevance
“…This was in tandem with our current gene expression analysis, which showed increased expression of inflammatory cytokines namely TNF-α and IL-6 following exposure to both PM2.5 and PM10. These results are in agreement with a previously reported studies in which PM2.5-10 increased the expression levels of the inflammatory markers including TNF-α and IL-1β in endothelial progenitor cells [37], IL-6 and IL-8 in monocytes [38], IL-6 in Kupffer cells [39] and TNF-α, IL-6 and IL-8 in lung epithelial cells [40]. The mechanism through which the airborne particulates induced apoptosis and increased the expression level of the inflammatory markers was attributed to triggering the formation of the reactive oxygen species (ROS) [37,40,41].…”
Section: Discussionsupporting
confidence: 94%
“…This was in tandem with our current gene expression analysis, which showed increased expression of inflammatory cytokines namely TNF-α and IL-6 following exposure to both PM2.5 and PM10. These results are in agreement with a previously reported studies in which PM2.5-10 increased the expression levels of the inflammatory markers including TNF-α and IL-1β in endothelial progenitor cells [37], IL-6 and IL-8 in monocytes [38], IL-6 in Kupffer cells [39] and TNF-α, IL-6 and IL-8 in lung epithelial cells [40]. The mechanism through which the airborne particulates induced apoptosis and increased the expression level of the inflammatory markers was attributed to triggering the formation of the reactive oxygen species (ROS) [37,40,41].…”
Section: Discussionsupporting
confidence: 94%
“…Recent studies showed that PM 2.5 exposure activates Kupffer cells in murine liver tissues, indicating that PM 2.5 represents a risk factor for NAFLD progression [1, 10, 13]. In this study, we used a “real-world” PM 2.5 exposure system, “Ohio’s Air Pollution Exposure System for the Interrogation of Systemic Effects (OASIS)”, to perform whole-body exposure of mice to environmentally relevant PM 2.5 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to genetic and diet-related factors, exposure to environmental pollutants has been shown to negatively affect key pathogenic events implicated in NAFLD. For instance, chronic inhalation of low levels of ambient air particulate matter (PM 2.5) has been was reported to induce hepatic steatosis and lipid peroxidation and, moreover, increase hepatic inflammatory and fibrosis stage in mice (Tomaru et al 2007, Tan et al 2009). Exposure to nitrosamines and nicotine has also been found to play critical roles in the pathogenesis of NAFLD (Tong et al 2009, Azzalini et al 2010, Friedman et al 2012.…”
Section: Introductionmentioning
confidence: 99%